Free Fatty Acid and α-Lactalbumin-Oleic Acid Complexes in Preterm Human Milk Are Cytotoxic to Fetal Intestinal Cells in vitro - Chetta, Katherine E.; Newton, Danforth A.; Wagner, Carol L.; Baatz, John E. (Frontiers in Nutrition, 2022)
Human milk, the best enteral selection for a preterm infant, becomes altered during freezing and soluble free fatty acid is generated over time. Free fatty acids may form complexes, such as the oleic acid-bound protein called HAMLET (human α-lactalbumin made lethal to tumor cells). We determined the in vitro biological activity of preterm human milk protein-oleic complexes (HAMLET-like complexes) and tested the hypothesis that laboratory-synthesized HAMLET exhibits cytotoxicity in human immature epithelial intestinal cell culture. Thirty-four milk samples from 15 mothers of hospitalized preterm infants were donated over time. Milk fractions were tested repeatedly for FHs 74 Int and HIEC-6 fetal cell cytotoxicity, using a sensitive viability assay. Protein and fatty acid identities were confirmed by Western blot, high performance liquid chromatography, and mass spectrometry. Cytotoxicity of intestinal cells exposed to milk increased respective to milk storage time (p<0.001) and was associated with free oleic acid (p=0.009). Synthesized HAMLET was cytotoxic in cultures of both lines. Preterm milk samples killed most cells in culture after an average 54 days in frozen storage (95% C.I. 34-72 days). After prolonged storage time, preterm milk and HAMLET showed a degree of cytotoxicity to immature intestinal cells in culture.